(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
sediments of Lattakia coast, the concentrations were of the order of ng/g in the studied sites. Several of phosphorous pesticides has been detected such as: Ethion, Coumaphos, Mevniphos, Naled, Disulfton, Methyl parathion. The total concentrations of the pesticides ranged from ΣOPPs=1280.55 ng /g in estuarine of Al-Kabir al-shemali river to ΣOPPs=1147.52 ng/g in Lattakia port. The results showed an increase in the concentration of Dichlorvos pesticide in all the studied sites, although it is forbidden to use it because of its danger to human health. The highest concentrations was 932.83 ng / g in Lattakia port, while the lowest concentration was 142.66 ng/g in estuarine of Ibn Hani site. The results showed the lowest mean concentrations of Diazinon, which were ranged between1.78 ng/g in Ibn Hani site and 0.2 ng/g in Lattakia port.